Digital competence of teachers in primary education: quantitative analysis of competence, use and attitudes towards new technologies in teaching - Sonia Janeth Romero Martínez; Carlos Jesús Hernández Lorenzo; Xavier Giovanni Ordóñez Camacho (Centro de Estudios Financieros, 2016)
The aim of the present work is to analyze the degree of digital competence (DC) of primary teachers and its relationship with the use of new technologies for teaching purposes. We also study the relationship between DC and attitude towards information and communications technnology (ICT) for the teaching process. To achieve this aims, the DC of 58 teachers of public and concerted schools were analyzed and comparisons according to age, gender, experience and type of school were performed. Also, a correlation between DC, use of ICT and attitude was made. Results show significant differences in DC according to age, gender, experience and type of school, but no differences according to attitudes towards ICT.